Stimulant medications effects in heat-related illness in ADHD patients: a large database study - Zinabu, Samrawit; Gasmelseed, Huda; Wheaton, Noah; Girma, Fikirte; Wong, Christian; Tabraiz, Sair Ahmad; Mubasher, Ayesha; Mack, Aaron; Lexima, Patrice; Qazi, Ozair; Mohammed, Ahmad; Sood, Aseem; et al. (Frontiers in Psychiatry, 2024)
IntroductionAttention Deficit Hyperactivity Disorder (ADHD), a prevalent neurodevelopmental disorder affecting a significant portion of the population, is commonly managed with stimulant medications. These medications, while effective, have been associated with thermoregulatory dysfunction and an increased risk of heat-related adverse events. The current study sought to compare the incidence of such events in ADHD patients receiving stimulant medications with those not on these treatments.MethodsA retrospective cohort study was conducted utilizing de-identified electronic medical records from a Global Research Network. The study population comprised ADHD patients on stimulant medication aged 6-24 years, with a comparison group of ADHD patients not receiving stimulant medications. Patients were followed from the date of first cohort inclusion (index event) for one year to track heat-related illnesses, including dehydration, hyperthermia, heat stroke, and other heat-related conditions. Propensity score matching was employed to balance baseline characteristics (age, gender) between cohorts. Risk ratios, odds ratios, and hazard ratios were calculated to assess the incidence of heat-related illnesses between groups. Statistical analysis was performed on the TriNetX platform, with survival analysis conducted via Kaplan-Meier estimates.ResultsAnalysis revealed a decreased risk of heat-related illnesses in the stimulant medication group, with a risk ratio of 0.559(95% CI: 0.485, 0.644). The mean number of events was also lower in the stimulants medication group (p=0.028). Additionally, Kaplan-Meier survival analysis indicated a higher probability of remaining free from heat-related illnesses in the stimulant group over a one-year period, with a statistically significant difference (log-rank test, χ² = 93.035, p < 0.0001).DiscussionThese results suggest that stimulant medications may be associated with a reduced risk of heat-related illnesses in ADHD patients, potentially contributing to better overall outcomes in this population. Further research is warranted to explore the underlying mechanisms and to confirm these findings across larger and more varied patient populations.